Lung Injury After One-Lung Ventilation: A Review of the Pathophysiologic Mechanisms Affecting the Ventilated and Collapsed Lung. Issue 3 (June 2016) - Lohser, Jens; Slinger, Peter
Abstract : (Abstracted from Anesth Analg, 121:302–318, 2015) One-lung ventilation (OLV) enables complex intrathoracic surgeries but has also become a recognized risk factor for acute lung injury (ALI). It is associated with increased postoperative pulmonary complications and histologic/biochemical lung injury in patients.